Experience Teaching To Pediatrics Students Of The Stomatological Faculty of Odessa International Humanitarian University - Nikitina, N. O.; Bespalova, A. V.; Kukushkin, V. N (Sergeieva&Co Karlsruhe, Germany, 2023)
The article presents the results of studying the assessment of teaching pediatrics to students of the Stomatological faculty of the International Humanitarian University. Pediatrics, along with therapy and surgery, is one of the basic disciplines in the formation of the clinical thinking of the future doctor. An analysis of the assimilation of pediatrics was carried out using traditional and innovative teaching methods with a combination of online and offline forms of education. In the course of the study, a scientific and informational search was carried out on the form and methods of teaching pediatrics to students of dental faculties in the foundations of the higher education of Ukraine and Europe, as well as the existing problems and ways to solve them, with a further comparative assessment of the methods and learning outcomes at International Humanitarian University. A comparative analysis of the methods of teaching pediatrics to students of the stomatological faculty at the Department of Obstetrics, Gynecology and Pediatrics showed high results in the assimilation of knowledge and skills through the use of traditional teaching in a children's clinic and modern innovative teaching and educational technologies based on information and material methods.

В роботі розглянуто теоретичні аспекти ринку праці регіону, проаналізовані авторські визначення сутності регіонального ринку праці. Розкрито сутність цілісної сукупності взаємопов’язаних елементів регіонального ринку праці, визначено та систематизовано структурні компоненти (елементи) ринку праці регіону, наведені характеристики формотворчих елементів ринку праці. Проаналізовані функції ринку праці, визначено та досліджено умови формування ринку праці регіону та окреслені завдання державного регулювання ринку праці на регіональному ринку.
ОПЫТ ОБУЧЕНИЯ ПЕДИАТРИИ СТУДЕНТОВ СТОМАТОЛОГИЧЕСКОГО ФАКУЛЬТЕТА ОДЕССКОГО МЕЖДУНАРОДНОГО ГУМАНИТАРНОГО УНИВЕРСИТЕТА
Nikitina N.O., Bespalova A.V., Kukushkin V.N. Experience Teaching To Pediatrics Students Of The Stomatological Faculty of Odessa International Humanitarian University // Modern engineering and innovative technologies. – Issue № 30, Part 3. – 2023. – P. 97-101. (DOI:10.30890/2567-5273.2023-30-00-037)
Keywords: pediatrics; students of the stomatological faculty; innovative teaching methods; educational technologies; педиатрия; студенты стоматологического факультета; инновационные методы обучения; образовательные технологии